Eutrofización de aguas residuales domiciliarias con absorción biológica de nitrógeno y fósforo, sector San José de Pichul, período 2021 – 2022. - Guanin Pallasco, Leysvin Camila (2022)
The release of untreated rural domestic graywater leads to an increase in the concentration of nutrients, especially nitrogen and phosphorus, causing significant changes in the structure of aquatic vegetation in adjacent water bodies. In the present study, a graywater phytoremediation system (Lemna minor) applied to a rural household environment was evaluated to extract eutrophying nutrients (N and P). Therefore, the total production (four months) of graywater in the household environment yielded a volume of 2.99 m3, which included effluent from hand washing, kitchen and laundry. The total production during the 6 weeks of the study was 4.43 m3. Next, the aquatic macrophyte (L. minor) used for phytoremediation in the pond, presented an initial density of 0.1 kg/m-2, and at the end 0.56 kg/m-2 was observed, detailing an exponential growth. In addition, the electrical conductivity of the treated water decreased from 2.6 to 0.15 µS/cm-1, in a linear decreasing trend. Then, the nutrient content analysis allowed quantifying an initial N concentration of 0.01 mg/l, which after 42 days of treatment with Lemna minor was reduced to 0.004 mg/l; meanwhile, P decreased from 14.7 to 0.27 ppm. In conclusion, a total nitrogen removal of 60% was demonstrated; in contrast, phosphorus reached an absorption efficiency of 98.16%.